Impact of CaNa2EDTA fortification on growth, antioxidant activity and stress-related gene expression in tilapia (Oreochromis niloticus) at different stocking densities paradigms - Wajeeha Komal; Shafaq Fatima; Qandeel Minahal; Razia Liaqat; Asma Abdul Latif; Aya S. Hussain (PLoS ONE, 2025)
Increasing aquaculture production requires high-density farming, which induces stress, necessitating supplements to mitigate its effects and ensure fish health. The aim of this study was to examine how CaNa2EDTA (EDTA) affects the growth, immune response and antioxidant activity in Nile tilapia (Oreochromis niloticus). The fish were raised at three different stocking densities: low (LD = 2.00 kg/m3), medium (MD = 3.50 kg/m3), and high (HD = 5.00 kg/m3). Each density group was fed with one of four levels of EDTA supplementation (E0 = 0 g/kg, E1 = 5 g/kg, E2 = 10 g/kg, and E3 = 15 g/kg) for 60 days. Each diet was tested in triplicate (n = 66 fish per replicate in LD, 116 per replicate in MD, and 166 per replicate in HD). After 60 days, the results of this study declared that LD group showed better growth than the MD and HD groups, and among all groups, those fed the E1 diet grew better than those on other diets. The study found significant changes in the chemical composition of the fish and the activity of digestive enzymes across all treatments. Antioxidant enzyme levels and cortisol were higher in the HD group compared to the LD and MD groups. However, fish in the HD group fed the E1 diet had the lowest levels of antioxidant enzymes and cortisol. Malondialdehyde levels were higher in the HD group compared to the LD and MD groups, with the lowest levels seen in fish on the E1 diet in the HD group. The expression of Somatostatin-1 did not increase in the MD group compared to the LD and HD groups. The gene expression levels of pro-opiomelanocortin-α and Interleukin 1-β were not significantly affected by either stocking density or EDTA supplementation. In conclusion, EDTA supplementation improved growth and antioxidant response in tilapia, with the best results seen at a dose of 5 g/kg in the high-density group, suggesting that this approach could be beneficial in intensive tilapia farming.